Improving the Performance of Justice Institutions - Decker, Klaus; Mohlen, Christian; Varela, David F. (World Bank, Colombia, 2017)
This paper presents a selection of experiences from Organization for Economic Cooperation and Development (OECD) countries in managing justice institutions which are the most relevant for performance improvement of their counterparts in Latin America. The scope of the paper is mostly limited to the courts, but comprises all types of courts: specialized courts as well as courts of general jurisdiction, civil as well as criminal and administrative courts, first instance as well as appellate and supreme courts. Issues of legal reform, judicial training, alternative dispute resolution or access for the poor are not considered in this paper. The first chapter provides an overview of the justice sector reform experience in Latin America over the last two decades, and how these reforms coincide with or follow OECD country trends. The second chapter outlines the context of the debates regarding the performance and quality of justice services in OECD countries prior to the 1990s. The third chapter discusses the transition from traditional justice reform approaches in OECD countries to the New Public Management (NPM) approaches that began in the 1990s. The fourth chapter presents five major cases of reforms in public expenditure, human resources, and organizational restructuring in the justice sectors of five different countries. The fifth chapter describes recent trends in OECD countries regarding quality controls in court service delivery which share approaches with the private sector. The paper concludes with some suggestions about areas where Latin American judiciaries may benefit from experiences of OECD countries.